2011
DOI: 10.1007/s10661-011-2071-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of road dust loadings and chemical characteristics using resuspension

Abstract: The contribution of fugitive dust from traffic to air pollution can no longer be ignored in China. In order to obtain the road dust loadings and to understand the chemical characteristics of PM(10) and PM(2.5) from typical road dust, different paved roads in eight districts of Beijing were selected for dust collection during the four seasons of 2005. Ninety-eight samples from 28 roads were obtained. The samples were resuspended using equipment assembled to simulate the rising process of road dust caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…These profiles are derived from scientific papers including fugitive dust from Chinese Loess Plateau (Cao et al, 2008), Asian dust source areas (Zhang et al, 2014b), north plain , southwest basin (Liu et al, 2016b) and other Chinese regions (Ho et al, 2003;Zhao et al, 2006;Han et al, 2009;Kong et al, 2011;Han et al, 2011;Chen et al, 2012;Han et al, 2014;Kong et al, 2014;Cheng et al, 2015), coal-fired boilers (Zhang et al, 2008;Wang et al, 2009;Pei et al, 2016), industrial sources (Zheng et al, 2013); biomass burning (Zhang et al, 2007;Zhang et al, 2012;Tao et al, 2015) and vehicle exhaust . Source profiles are also collected from source apportionment studies in Chinese cities such as Beijing, Tianjin, Chongqing and so on.…”
Section: Structure Of the Databasementioning
confidence: 99%
“…These profiles are derived from scientific papers including fugitive dust from Chinese Loess Plateau (Cao et al, 2008), Asian dust source areas (Zhang et al, 2014b), north plain , southwest basin (Liu et al, 2016b) and other Chinese regions (Ho et al, 2003;Zhao et al, 2006;Han et al, 2009;Kong et al, 2011;Han et al, 2011;Chen et al, 2012;Han et al, 2014;Kong et al, 2014;Cheng et al, 2015), coal-fired boilers (Zhang et al, 2008;Wang et al, 2009;Pei et al, 2016), industrial sources (Zheng et al, 2013); biomass burning (Zhang et al, 2007;Zhang et al, 2012;Tao et al, 2015) and vehicle exhaust . Source profiles are also collected from source apportionment studies in Chinese cities such as Beijing, Tianjin, Chongqing and so on.…”
Section: Structure Of the Databasementioning
confidence: 99%
“…On the other hand, taking into account that one of the main primary contributors to indoor particles is probably resuspended dust, some of which associated with soil, high OC/EC ratios are not surprising. In fact, it has been reported that particles from dust resuspension present high OC/EC ratios (e.g., Amato et al, 2009;Chen et al, 2012). The poor indoor-outdoor correlations of OC (r 2 between 0.22 and 0.30) indicate the presence of multiple carbon sources, and different contributions to indoor and outdoor carbonaceous particles.…”
Section: Particulate Matter Levels and Chemical Compositionmentioning
confidence: 99%
“…The contribution of road dust particles to atmospheric particulate pollution through resuspension has been studied in many cities around the world (Table 4), and such particles have been found to contribute 16-56% and 8-19% to PM 10 and PM 2.5 , respectively (Amato et al, 2009a;Avino et al, 2014;Bukowiecki et al, 2010;Chen et al, 2012;Fan et al, 2007;Karanasiou et al, 2011;Kuhns et al, 2001;Song et al, 2006). However, the amounts of various pollutants in resuspended road dust have been assessed in very few studies, and this severely hampers the ability to reliably assess the acute impacts of atmospheric particulate pollution.…”
Section: Contribution Of Road Dust Particles To Atmospheric Particulamentioning
confidence: 99%
“…At present, air quality degradation due to ambient particulate matter has become an environmental issue of public health concern in most metropolitan areas in China (Chen et al, 2012;Huang et al, 2014). It is well known that the resuspension of road dust particles from urban street surfaces is an important source of atmospheric particulate pollution (Amato et al, 2009b;Martuzevicius et al, 2011).…”
Section: Introductionmentioning
confidence: 99%